2019
DOI: 10.1111/jcmm.14407
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid differentiation protein 1 protected myocardial function against high‐fat stimulation induced pathological remodelling

Abstract: Myeloid differentiation 1 (MD‐1) is a secreted protein that regulates the immune response of B cell through interacting with radioprotective 105 (RP105). Disrupted immune response may contribute to the development of cardiac diseases, while the roles of MD‐1 remain elusive. Our studies aimed to explore the functions and molecular mechanisms of MD‐1 in obesity‐induced cardiomyopathy. H9C2 myocardial cells were treated with free fatty acid (FFA) containing palmitic acid and oleic acid to challenge high‐fat stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…MitoQ ameliorated the increase in CPT1A, CycloF, and Cyto C induced by PA in these cells, in agreement with our in vivo data. It has consistently been reported that PA interferes with several signaling pathways, including the Erk and NF-κB pathways [58,59]. Therefore, these data suggest interactions between lipotoxicity and mitochondrial oxidative stress, which regulate downstream events responsible for cardiac alterations in the context of obesity.…”
Section: Discussionmentioning
confidence: 60%
“…MitoQ ameliorated the increase in CPT1A, CycloF, and Cyto C induced by PA in these cells, in agreement with our in vivo data. It has consistently been reported that PA interferes with several signaling pathways, including the Erk and NF-κB pathways [58,59]. Therefore, these data suggest interactions between lipotoxicity and mitochondrial oxidative stress, which regulate downstream events responsible for cardiac alterations in the context of obesity.…”
Section: Discussionmentioning
confidence: 60%
“…Obesity-related cardiac remodeling is the important pathological manifestation of sudden cardiac death (SCD) [15]. In earlier work, our group found that HFD could induce pathological cardiac remodeling and increase susceptibility to VA [9]. Moreover, excessive APD prolongation is a hallmark of the abnormally altered electrophysiology or adverse electrical remodeling [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies found that MD1 expression was downregulated in heart failure patients [6,7], and loss of MD1 could worsen structural and electrical remodeling under pressure overload and ischemia/reperfusion injury conditions via increased the activation of the TLR4 signaling pathway [6,8]. Interestingly, we also found that MD1 deletion had no significant effect on the cardiac structure in wild-type (WT) mice under physiological conditions [6][7][8][9][10][11]. Moreover, downregulated MD1 does not activate the TLR4 signaling pathway in both in vitro and in vivo experiments [7,9].…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations